Association Between Household Income and Fruit-Vegetable Expenditure and the Intake of Vitamins and Minerals in Pontianak City - Fadly, Dzul (Journal of Health and Nutrition Research, 2024)
This study explores the association between household income, fruit and vegetable expenditure, and the intake of selected micronutrients among urban households in Pontianak City. A cross-sectional survey was conducted on 100 households, collecting dietary data on calcium, phosphorus, iron, and vitamins A, B, and C using a 24-hour recall method. Socioeconomic data included monthly income and expenditure on fruits and vegetables. Pearson and Spearman correlation tests assessed the strength and direction of bivariate relationships, while multiple linear regression evaluated the combined effects of income and food expenditure on nutrient intake. Results showed that average household income was Rp 4,382,730, with a mean fruit and vegetable expenditure of Rp 294,880. Vitamin C intake exhibited a very strong and statistically significant correlation with income (Pearson r = 0.998; p < 0.001), and regression analysis confirmed income as a significant predictor (p < 0.001; R² = 0.996). Calcium intake was significantly associated with fruit and vegetable expenditure (p < 0.001; R² = 0.999), indicating that food purchasing behavior may more strongly influence calcium consumption. No significant associations were found between income or expenditure and the intake of vitamin A, vitamin B, iron, or phosphorus. These findings suggest that economic factors selectively influence micronutrient intake, where income plays a critical role in access to vitamin C-rich foods, while expenditure patterns relate more closely to calcium sources. Nutritional interventions in urban areas should consider both economic capability and consumption behavior to effectively address micronutrient deficiencies.